Pengaruh Media Sosial terhadap Kesehatan Mental pada Anak Muda di Indonesia - Erzha Tri Setyo Rochman; Septiana Mukti; Nazwa Mahabatul Thigah Yanani; Fita Sinta Dewi; Liss Dyah Dewi A (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In this era of advanced technology, humans no longer only interact with others directly, but also people can interact indirectly, That is with the presence of social media technology. By using social media, one is free to comment and share opinions with other users without worry. However, in the use of social media is often used to create good feelings, without realizing it, social media can backfire on its users so that it can cause bad things. In addition to being able to have a powerful effect on user behavior, social media. This study aims to determine the impact of cyberbullying on social media and find out how to overcome it. The method used is qualitative by taking data through the distribution of Google Forms to social media users aged 13-25 years. This research is useful for increasing concern for fellow humans, especially regarding mental health. In a survey of 45 respondents, there were 95.6% who said that cyberbullying cases in Indonesia have occurred a lot. This shows that the condition of cyberbullying in Indonesia is already at a high level. Therefore, cyberbullying should be taken seriously.